Analisis Kinerja Keuangan PT Bank Mega Syariah - Budi Gautama Siregar; Aswadi Lubis (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2023)
This study aims to analyze the financial performance of PT. Bank Mega Syariah uses a liquidity ratio proxied by the Financing to Deposit Ratio (FDR), Capital Adequacy Ratio (CAR), Return on Assets (ROA) and Return on Equity (ROE). This type of research is descriptive quantitative by analyzing then describing the results to describe the bank's financial performance. This research uses secondary data, namely the financial statements of PT. Bank Mega Syariah from the 2013-2021 period. The results found that in terms of the Financing to Deposit Ratio (FDR) it was found that PT. Bank Mega Syariah experienced fluctuations, but in 2015 in the second and third quarters with a ratio of 104.19% and 102.89%. Analysis of Capital Adequacy Ratio (CAR) obtained that PT. Bank Mega Syariah has a very good CAR. In the ROA analysis, there are several unhealthy conditions in accordance with the provisions issued by Bank Indonesia, namely in 2016.